The Effect of Red Spinach Juice + Fe Tablets on Increased Hemoglobin Levels in Pregnant Women - Mariati; Afrina Mizawati; Tonny C Maigoda (Postgraduate, University of Mataram, 2023)
Anemia during pregnancy is one of the most common abnormalities in pregnant women in Indonesia. The prevalence of anemia in pregnant women in Indonesia is 48.9%. The iron supplementation program is an effort that has been made by the Indonesian government to prevent anemia. To determine the effect of giving red spinach juice on increasing hemoglobin levels in third-trimester pregnant women. This type of research uses quantitative methods with quasi-experimental research with the two-group approach. The experimental group consumed red spinach juice + Fe tablets and the control group only drank Fe tablets. The results showed that there was an effect of giving red spinach juice + Fe tablets to increasing hemoglobin levels and there was a difference in increasing hemoglobin levels in the group given red spinach juice + Fe tablets and Fe tablets only. There is a relationship between parity and an increase in hemoglobin levels, but there is no relationship between age and education and an increase in hemoglobin levels. Intervention and parity variables were the most influential variables in increasing the hemoglobin level of pregnant women in PMB Bengkulu City. Results: There is an effect of giving red spinach juice + Fe tablets to the increase in hemoglobin levels of pregnant women.